Comparative study of actuation systems for portable upper limb exoskeletons. (October 2018) - Manna, Soumya K; Dubey, Venketesh N.
Highlights: Combine both active and passive modes of operation in a single platform for better recovery. Allow active variable gravity compensating mechanism for different torque requirements. Joint stiffness changing mechanism to have different levels of difficulty. The system should operate passively wherever possible to make it energy efficient. The system should not compromise with the safety features at any point. Abstract: During the last two decades, a large variety of upper limb exoskeletons have been developed. Out of these, majority are platform based systems which might be the reason for not being widely adopted for post-stroke rehabilitation. Despite the potential benefits of platform-based exoskeletons as being rugged and reliable, stroke patients prefer to have a portable and user-friendly device that they can take home. However, the types of actuator as well as the actuation mechanism used in the exoskeleton are the inhibiting factors why portable exoskeletons are mostly non-existent for patient use. This paper presents a quantitative analysis of the actuation systems available for developing portable upper arm exoskeletons with their specifications. Finally, it has been concluded from this research that there are not many stand-alone arm exoskeletons which can provide all forms of rehabilitation, therefore, a generic solution has been proposed as the rehabilitation strategy to get best out of the portable arm exoskeletons.